2020
DOI: 10.3390/cells9112476
|View full text |Cite
|
Sign up to set email alerts
|

Complex Interaction between Resident Microbiota and Misfolded Proteins: Role in Neuroinflammation and Neurodegeneration

Abstract: Neurodegenerative diseases such as Alzheimer’s disease (AD), Parkinson’s disease (PD) and Creutzfeldt–Jakob disease (CJD) are brain conditions affecting millions of people worldwide. These diseases are associated with the presence of amyloid-β (Aβ), alpha synuclein (α-Syn) and prion protein (PrP) depositions in the brain, respectively, which lead to synaptic disconnection and subsequent progressive neuronal death. Although considerable progress has been made in elucidating the pathogenesis of these diseases, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 225 publications
(175 reference statements)
1
32
0
Order By: Relevance
“…In lipopolysaccharide (LIP) -induced MIA progenies, MIA progenies exhibited an abnormal brain-gut-microbiome axis compared with that of the control progenies, which were characterized by social behavioral deficits, anxiety-like and repetitive behaviors, low myelination, and ASD-like microbiome [66]. Studies have shown a potential link between host microbiome (such as gut and oral bacteria), neuroinflammation, and dementia, which may be caused by bacterial invasion of the brain due to barrier leakage, toxin and inflammation factor production, or indirectly by modulating immune responses, and moreover, the composition of microbiota affected the deposition level of Aβ in the cerebral cortex of APP/PS1 mice [67], suggesting a critical role of iron in these processes.…”
Section: Roles Of Microbiota In Iron Homeostasis and Neurodegenerative Diseasesmentioning
confidence: 99%
“…In lipopolysaccharide (LIP) -induced MIA progenies, MIA progenies exhibited an abnormal brain-gut-microbiome axis compared with that of the control progenies, which were characterized by social behavioral deficits, anxiety-like and repetitive behaviors, low myelination, and ASD-like microbiome [66]. Studies have shown a potential link between host microbiome (such as gut and oral bacteria), neuroinflammation, and dementia, which may be caused by bacterial invasion of the brain due to barrier leakage, toxin and inflammation factor production, or indirectly by modulating immune responses, and moreover, the composition of microbiota affected the deposition level of Aβ in the cerebral cortex of APP/PS1 mice [67], suggesting a critical role of iron in these processes.…”
Section: Roles Of Microbiota In Iron Homeostasis and Neurodegenerative Diseasesmentioning
confidence: 99%
“… 196 , 223 Furthermore, they possess receptors which react to the overproduced Aβ. 224 , 225 The most important receptors are the TLRs, in particular TLR4, 199 , 226 , 227 which initiate intracellular signaling pathways leading to the activation of the NF-κB, the inflammasome and the antiviral molecular machinery. 228 At the end of this process, activated microglia become senescent and only produce pro-inflammatory neurotoxic mediators such as TNFα.…”
Section: Brain Antimicrobial Immunitymentioning
confidence: 99%
“…Therefore, while OM-MSA and OM-PD samples were able to generate αSyn_RT-QuIC products with distinctive properties, the in vitro generated αSv1, αSv2 and αSv3, although characterized by different morphological features, did not. For this reason, we hypothesized that only the αSyn D strains present in OM samples and likely other tissue factors (e.g., microbiota [ 43 ]) could markedly influence the misfolding process of rec-αSyn and the biochemical and morphological features of the RT-QuIC products. Hence, αSv1, αSv2 and αSv3 produced from rec-αSyn, lacked peculiar features which are present in the natural α-synuclein strains (e.g., phosphorylation) that could play a role in this process.…”
Section: Resultsmentioning
confidence: 99%